SMS writting from the perspective of its users. An approach about the Galician language - Mosquera Castro, Estefanía (Madrygal. Revista de Estudios Gallegos, 2013)
This paper examines the characteristics of text messaging, the application of the Information and Communication Technologies which has experimented the fastest growing and which has established itself in recent times as one of the most expressive communicative elements of the Electronic Age. Our research parts from the premises of the Perceptive Linguistic and through the results of a survey we will indicate what the Galician judge on this means of communication and on the features of texting –SMS language– that comes associated with it. Alike, we will determine –according to their considerations– the profile of users, the main reasons that motivated the sucess of this tool and the purpose for which it is used. And finally, we will also carry out an approach to the linguistic properties of the SMS and, likewise, we will study its social status and its significance in other contexts.
Keywords: text-messages; texting; Perceptive Linguistic; Galician language